Electrostatic Interaction and Reaction Behavior of a 1, 2, 4‐Triazole Mixture with Dinitrobenzene. Issue 5 (27th January 2015) - Sasahara, Kohei; Kumasaki, Mieko; Date, Shingo; Koshi, Mitsuo
Abstract The electrostatic interactions between gas generating agent and organic electron withdrawing additives were studied to understand how the interaction affects the reactions of their thermal behavior. To explore the electronic interaction and its effect, the thermal behavior of a mixture of dinitrobenzene isomers [p‐dinitrobenzene (pDNB) and m‐dinitrobenzene (mDNB)] and 1, 2, 4‐triazole (TA) was analyzed. Density functional calculations and electron density analysis proved that both pDNB and mDNB in a 1:1 ratio withdraw electrons from TA. The analysis of pyrolysis behavior showed that TA and dinitrobenzene mixtures (TA/pDNB or TA/mDNB) react at lower temperatures than each precursor. Gas chromatography mass analysis and UV/Vis spectroscopy showed reasonable results that suggested that pDNB and TA make condensed products in the initial stage of the reaction according to the differential scanning calorimetry measurement. When the mixtures were ignited under pressurized conditions, TA/pDNB burned easily while TA/mDNB burned only partially. These results suggested that the interaction between triazole and dinitrobenzene affects the pyrolysis and combustion behavior of a TA/dinitrobenzene mixture.